Investigation Of Taste Masking Techniques And Development Of Dapoxetine Hcl Orally Disintegrating Tablet - Liew, Kai Bin (2017)
In the development of orally disintegrating tablets (ODT), palatability plays a critical role. As there were hardly any reported studies on taste masking of drugs which cause burning sensation on oral mucosa and is bitter in taste, dapoxetine HCl was chosen for the study. Various taste masking techniques, namely complex formation with ion exchange resin, coating with pH sensitive polymer, coating with hydrophilic polymer, chemical modification, addition of sweetener and flavour, inclusion complexation and blending with inorganic compound, were investigated.